EVALUATION OF THE INTERNAL CONTROL APPLICATION FOR THE PROCESS OF ACCEPTANCE AND RETURN OF COLLATERAL AT PT. PEGADAIAN (PERSERO) UPC RATAHAN - Sumangando, Thivany Icci; Nangoi, Grace B. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2015)
PT. Pegadaian (Persero) UPC Ratahan is a non-bank financial institution for the community that provides credit loans with collaterals requirements. The collaterals must be in good condition when they are returned to the customers. Therefore, PT. Pegadaian (Persero) UPC Ratahan must hold an internal control for the process of acceptance and return of collaterals. That is why the purpose of this study is to evaluate the application of internal control for the process of acceptance and return of collaterals at PT. Pegadaian (Persero) UPC Ratahan whether it is in accordance with the five control components of the COSO. The method that was used in this research is descriptive research method. The results shows that the internal control of PT. Pegadaian (Persero) UPC Ratahan was in a good criteria. Although there are still some shortcomings during the transaction process, when the transaction was completed, the collaterals is not immediately be stored and recorded but it only stacked in a drawer or desk, as well as the organization structure is not maximized for the division of duties, the manager also becames a warehouse clerk as well as estimator. It would be better if the organizational structure of PT. Pegadaian (Persero) UPC Ratahan are added with some employees and the recording and storage of the collaterals should be done immedaitely after the collaterals have been receive and assessed. Keywords: mortgage, internal control, collateral